1999
DOI: 10.1074/jbc.274.44.31435
|View full text |Cite
|
Sign up to set email alerts
|

Different Functional Aspects of the Group II Subfamily (Types IIA and V) and Type X Secretory Phospholipase A2s in Regulating Arachidonic Acid Release and Prostaglandin Generation

Abstract: We have recently reported that members of the heparin-binding group II subfamily of secretory PLA 2 s (sPLA 2 s) (types IIA and V), when transfected into 293 cells, released [ 3 H]arachidonic acid (AA) preferentially in response to interleukin-1 (IL-1) and acted as "signaling" PLA 2 s that were functionally coupled with prostaglandin biosynthesis. Here we show that these group II subfamily sPLA 2 s and the type X sPLA 2 behave in a different manner, the former being more efficiently coupled with the prostaglan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
195
2
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(220 citation statements)
references
References 52 publications
(128 reference statements)
22
195
2
1
Order By: Relevance
“…PLA 2 , however, is the only phospholipase that seems to be able to release free AA directly in a single-step reaction, by hydrolysing an ester bond at the sn-2 position of phospholipids [8], which is why it features as the main phospholipase of interest in most literature in connection with AA metabolism. Mammalian cells contain several isoforms of the enzyme PLA 2 [ 9 ], which receive their stimulatory signals from a vast range of inflammatory signals, cytokines, growth factors and hormones.…”
Section: The Arachidonic Acid Cascadementioning
confidence: 99%
“…PLA 2 , however, is the only phospholipase that seems to be able to release free AA directly in a single-step reaction, by hydrolysing an ester bond at the sn-2 position of phospholipids [8], which is why it features as the main phospholipase of interest in most literature in connection with AA metabolism. Mammalian cells contain several isoforms of the enzyme PLA 2 [ 9 ], which receive their stimulatory signals from a vast range of inflammatory signals, cytokines, growth factors and hormones.…”
Section: The Arachidonic Acid Cascadementioning
confidence: 99%
“…Several other activation mechanisms have been proposed to account for sPLA 2 interactions with cells. Membrane pertubation by phospholipid scramblase has been proposed to contribute to sensitization of cells toward the action of sPLA 2 (68). Other studies have demonstrated that cPLA 2 ␣ is required for group IIa or V PLA 2 s to act properly (26,67,69,70).…”
Section: Role Of Constitutively Activated Erk1/2 On H 2 O 2 -Induced Aamentioning
confidence: 99%
“…These observations raise the possibility that the site of fatty acid release by hGIIA is within intracellular vesicles. In contrast, the non-heparan sulfate-binding hGX is thought to act on the extracellular face of the plasma membrane of HEK293 cells and does not accumulate in intracellular domains (18). It is not yet known whether there is a biochemical connection between IL-1␤-induced arachidonate release and intracellular action of hGIIA.…”
mentioning
confidence: 93%
“…hGX is not a highly basic protein and accumulates in the extracellular medium when transfected in HEK293 cells (18). Whereas serum stimulates arachidonate release from both hGIIA-and hGX-transfected HEK293 cells, only the former cells show an additional increase in fatty acid release if the pro-inflammatory cytokine interleukin-1␤ (IL-1␤) is added along with serum (18). The biochemical basis for this cytokine effect is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation